Capital structure decisions in family firms: empirical evidence from a bank-based economy - Markus Ampenberger; Thomas Schmid; Ann-Kristin Achleitner; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2009)
This study examines how family firm characteristics affect capital structure decisions. In our analysis we disentangle the influence of three distinct components of a family firm: ownership, supervisory and management board activities by the founding family. Thereby, we use a unique panel dataset of 660 publicly listed companies (5,135 firm years) in the broadest German stock index CDAX from 1995 to 2006. This paper is motivated by hitherto inconclusive empirical findings on capital structure decisions in family firms from Anglo-Saxon countries. We provide new evidence for a bank-based economy. In this sense, Germany provides a very fruitful research environment as it (i) traditionally has a bank-based financial system and (ii) family firms are considered to be the backbone of the economy. We find that family firms have significantly lower leverage ratios than non-family firms, independent of the definition of leverage applied. Among the three dimensions of a family firm, management board involvement by the founding family has a consistently negative influence on leverage across all our models. In contrast, the influence of ownership and supervisory board representation is insignificant in almost all of our models. In line with agency theory, we can show that the leverage level is the lowest if the founding family is simultaneously a large shareholder with monitoring incentives and involved in firm management with convergence-of-interest effects. Finally, we detect that the presence of a founder CEO in firm management has a significant negative effect on the leverage ratio. Our results prove to be stable against a battery of robustness tests including a matching estimator technique to demonstrate causal effects.
Keywords: G32; G34; 330; family firms; family ownership; family management; founder CEO; agency costs; capital structure; debt-equity ratio; leverage; corporate governance; risk aversion; Familienunternehmen; Eigentümerstruktur; Kapitalstruktur; Prinzipal-Agent-Theorie; Corporate Governance; Risikoaversion; Finanzierungstheorie